Modelo de regeneración urbana sostenible en sectores con asentamientos informales en Barranquilla, Colombia (2019)
In Colombia, as in other countries, there are factors that stimulate the development of informal settlements and, consequently, innumerable socioenvironmental problems. The objective of the article is to propose a model of sustainable urban regeneration for land recuperation applicable in informal human settlements. The research is quantitative-qualitative, structured in three phases of study. The result of the investigation includes typological alternatives of housing, increase in housing densities and efficiency in the use of land.